Effect of Different Levels of Energy and Protein in Total Mixed Ration on Body Weight, Body Condition Score and Body Measurement in Crossbred Heifer-Calves - Trivedi, Pankaj G; Lunagariya, Pravin M; Vaidh, Palak P; Parmar, Chirag P; Sorathiya, Kamlesh K (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
The experiment was aimed to evaluate the impact of varying energy and protein levels in a total mixed ration on body weight, body weight gain, body condition score (BCS), and body measurement in crossbred heifer-calves. A total of 24 crossbred heifer-calves (75% Holstein Friesian x 25% Kankrej) 4-6 months old, with similar growth and body weight were randomly allocated to four treatment groups, each consisting of six calves. The calves in groups T1, T2, T3, and T4 were fed TMR having 12.60% crude protein (CP) & 2.028 Mcal metabolizable energy (ME)/kg feed, 14.30% CP & 2.131 Mcal ME/kg feed, 15.98% CP & 2.244 Mcal ME/kg feed, and 17.58% CP & 2.307 Mcal ME/kg feed, respectively, for 140 days. The mean body weight was not significantly (p>0.05) affected among treatment groups, while total body weight gain (kg) and heart girth gain (cm) were significantly (p<0.05) higher in high ME CP groups (T3, T4) than lower ME CP groups (T1, T2) of calves. The body condition score and daily body weight gain (kg/day) was significantly (p<0.05) higher in T4 group followed by T2 and T3 groups and lowest in T1 group. The body measurement (heart girth, height at wither, body length) and their gain (height at wither, body length) were statistically non-significant (p>0.05) among treatment groups. The higher energy and protein levels in total mixed ration increased total and daily body weight gain and body condition score in crossbred heifer-calves.